Strategi Kreatif Komunikasi Pemasaran Digital Pada Wisata Museum di Jakarta Barat - Cahyowati, Tridiah; Ardha, Berliani (Universitas Mercu Buana, 2022)
The government is currently trying to manage museums in Indonesia and attract the interest of the millennial generation. Currently, the number of visits to the National Museum, Jakarta History Museum, Ceramic Museum and other museums in Jakarta is still low. In fact, these museums are one of the tourist destinations that can be visited by tourists. Therefore, the number of visits still needs to be increased in order to compete with the habits of the millennial generation who often visit shopping centers. The Old City area in Taman Sari District, located in West Jakarta, is a favorite tourist destination for local and foreign tourists. The strength of the Old City area is the existence of Dutch heritage buildings and several museums that are located close together, namely the Jakarta History Museum, the Wayang Museum, the Ceramic and Ceramic Fine Arts Museum and several local Indonesian bank museums such as the BNI Museum (Bank Negara Indonesia 1946), the Bank Mandiri Museum and the Bank Indonesia Museum. Based on the above, researchers are interested in researching Creative Strategies for Museum Tourism in Jakarta.